Modifying the Structure of Multiwalled Carbon Nanotubes with Continuous and Pulsed Ion Beams; Physics of the Solid State; Vol. 60, iss. 12 - Korusenko P. M. Petr Mikhaylovich; Nesov S. N. Sergey Nikolaevich; Povoroznyuk S. N. Sergey Nikolaevich; Bolotov V. V. Valery Viktorovich; Knyazev E. V. Evgeny Viktorovich; Pushkarev A. I. Aleksandr Ivanovich; Smirnov D. A. Dmitry Aleksandrovich (2018, 2018)
Title screen